KEKSARGANDA QANDAY OVQATLANGAN MA’QUL? - Qurbonov, Shoniyoz; Yarqulova, Maftuna (MODERN PROBLEMS AND PROSPECTS FOR ORGANIZING A HEALTHY LIFESTYLE AND PROPER NUTRITION, 2024)
KEKSARGANDA QANDAY OVQATLANGAN MA’QUL?